2011
DOI: 10.4314/tjpr.v10i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Cosmeceuticals for Photoprotection from Ultraviolet B Radiation: A Review

Abstract: Ultraviolet B (UVB) rays vary with time and season and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 35 publications
1
58
0
4
Order By: Relevance
“…Lipid peroxidation is one of the sequels of superoxide anion generation [23]. One possible method to prevent skin from UV damage is to use a powerful antioxidant to quench the generated ROS [24]. The results of this study showed that EGCG suppressed the increase in levels of superoxide anion and MDA of the HSF cells exposed to UV A (Figures 4-5), resulting in the increase of HSF viability ( Figure 3).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Lipid peroxidation is one of the sequels of superoxide anion generation [23]. One possible method to prevent skin from UV damage is to use a powerful antioxidant to quench the generated ROS [24]. The results of this study showed that EGCG suppressed the increase in levels of superoxide anion and MDA of the HSF cells exposed to UV A (Figures 4-5), resulting in the increase of HSF viability ( Figure 3).…”
Section: Discussionmentioning
confidence: 69%
“…The more OH groups it has, the stronger its power to fight against UV stressed skin aging [28,29]. EGCG is the ester of epigallocatechin and gallic acid, and so its molecule has more OH groups than EC, thus making EGCG a stronger potential candidate as a dermatological protectant.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the number of plant species used in skin care, cosmetics and fragrances is considerably greater and continues to grow: sabal (Serenoa serrulata (Michx.) G. Nicholson) [56], gooseberry (Phyllanthus emblica L.) [57], (Matricaria chamomilla L.) [58], pomegranate (Punica granatum L.) [59], mango (Mangifera indica L.) [60], gotu kola (Centella asiatica (L.) Urb.) [61], and many others.…”
Section: Presentmentioning
confidence: 99%
“…Herbal cosmeceuticals are often used in sunscreens as a barrier to protect skin from the harmful UV rays (104).…”
Section: Sunburnmentioning
confidence: 99%